UV curable hyperbranched polyester polyurethane acrylate for hydraulic machinery coating - Yuan, Mengjie; Wang, Shuai; Li, Guixun; He, Suqin; Liu, Wentao; Liu, Hao; Huang, Miaoming; Zhu, Chengshen (Materials research express, 2021)
The content of river cement and sand in our country is relatively high, and the surface of hydraulic machinery in hydropower stations is often subject to fatigue damage and erosion. This topic is mainly used to solve the problem of abrasion and corrosion of hydraulic machinery coatings. UV curable polyurethane acrylate (PUA) can be quickly solidified into film and directly coated on the surface of hydraulic machinery with excellent anti-wear, adhesion properties and low cost. In this work, a hyperbranched polyester synthesized by the stepwise reaction of trimethylolpropane (TMP) and dimethylolpropionic acid (DMPA) was as a ‘nucleus’, and the polyurethane prepolymer was obtained by grafting IPDI and PTMG (C Schüll, H Frey, 2013 Grafting of hyperbranched polymers: from unusual complex polymer topologies to multivalent surface functionalization, Polymer , 54, 5443–5455). The UV-curing hyperbranched polyester polyurethane acrylate (PUA-1) was prepared by capping with HEA (Xu, W, Wang, W, Hao, L, Zhao, W, Liu, H, Wang, X 2020 Effect of generation number on properties of fluoroalkyl‐terminated hyperbranched polyurethane latexs and its films. J. Appl. Polym. Sci. , e49215). Another UV-curing hyperbranched polyester polyurethane acrylate (PUA-2) was prepared as comparison by using TDI and PTMG as the main raw materials. Fourier Transform Infrared Spectrometer, 1 H-nuclear magnetic resonance spectroscopy, Gel Permeation Chromatography, thermogravimetric analysis and dynamic thermomechanical analysis were used to characterize its structure and properties. The wear rate of the two hyperbranched polyesters measured by the underwater steel ball method is below 3%, The swelling rate of PUA-1 is between 250%–300%, and the swelling rate of PUA-2 is around 260%, indicating that PUA-2 has better solvent resistance than PUA-1, and the internal structure of the film is more dense. TG analysis showed that the thermal stability of the two materials was good.